The birthday cake [videorecording (Blu-Ray)] - Giannopoulos, Jimmy; Giannopoulos, Jimmy; Fernandez, Shiloh, 1985-; Fernandez, Shiloh, 1985-; Fernandez, Shiloh, 1985-; Kilmer, Val, 1959-; McGregor, Ewan, 1971- (Screen Media, 2021)
When a young man brings a cake to his mobster uncle's house to commemorate his slain father's birthday, he witnesses a murder and begins to piece together the truth about his father's death.